O perfil das parturientes e seus recém-nascidos: a busca da assistência em município de tríplice fronteira - Triaca, Leonardo Pereira (2017)
Answering to the integration policy of the Mercado Comum do Sul (MERCOSUL) Brasil created in 2006 the Sistema Integrado de Saúde das Fronteiras (Integrated Health System of the Frontiers) (SIS-Fronteiras) aiming to rationalize the offer of health service and to improve the infrastructure already in existence in Brazilian border cities. The health of pregnant women was one of the main topics approached in the city of Foz do Iguaçu, Paraná, especially the Brazilian women living in Paraguay, also called Brasiguaias, who generally seek care for prenatal care and delivery, significantly interfering epidemiological data. As a result, it was created in 2007, the Centro Materno Infantil (Maternal and Child Health Center) offering free and quality prenatal care to these pregnant women, who also seek care at the time of childbirth, and for this they use the care center´s pregnant at the Ministro Costa Cavalcanti Hospital, a hospital which is Reference for high-risk deliveries and maternal complications. In this context, it is important to highlight the necessity of scientific studies that bring the health of Brasiguaian pregnant women as a focus of study, considering its importance on the result of the delivery, specially in what refers to the conditions of the parturients, fetuses and newborns. In this aspect, this study aims to describe the profile of parturients and their newborns in a reference hospital, among users who performed prenatal care at the Maternal and Child Health Center in Foz do Iguaçu - Paraná, in the period from January 2010 to December 2016. This is a descriptive, cross-sectional study with a quantitative approach, in which 15 variables were analyzed referring to parturients and their newborns, searched through electronic records and records books of the care center´s pregnant. Regarding the parturients, it was verified that 97.71% presented a public social security; 70.23% were between 20 and 34 years old; 67.18% had normal delivery; 76,34% parturients were Brazilian; and only 36.64% had 7 or more prenatal consultations. Regarding the conditions of the newborn, it was verified that only 6.05% presented low weight; 92.06% of term newborns (≥ 37 weeks and ≤ 41 weeks); 94.52% presented Apgar 1 ≥ 7 and 98.30% presented Apgar 5 ≥ 7; 96.22% were referred to the Joint Accommodation; Women who performed 7 or more prenatal consultations had a higher frequency of full-term infants, and Apgar at 1 minute less than 7 was significantly more frequent among those who delivered between 1 and 3 appointments. The present study identified a prevalence of parturients and newborns in favorable conditions, however, the results found allow us to recognize the necessity to invest in specific actions, directly influenced by the health indicators of these pregnant women and in the situation before the local health services.